Factors Related to Giving Formula Milk to Infants 0-6 Months in Pangurabaan Village, Sipirok District, South Tapanuli Regency in 2020 - Sri Lasmawanti; Veronica Anggreni Damanik (Institute of Computer Science (IOCS), 2021)
Breastfeeding is one of the first steps for a human being to get a healthy and prosperous life. This is stated in the Sustainable Development Goals (SDGs) or sustainable development goals in 2030. However, in several developed and developing countries including Indonesia, many career mothers are not breastfeeding exclusively. The research objective was to determine the factors associated with giving formula milk to infants 0-6 months in Pangurabaan Village, Sipirok District, Tapanuli Selatan Regency in 2020. The research design was a survey analytic study with a cross sectional approach. The population in this study were 60 mothers who gave formula milk to babies 0-6 months in Pangurabaan Village, Sipirok District, Tapanuli Selatan Regency. Data analysis used univariate and bivariate analysis using the chi-square test. The results of the study were based on the frequency of mothers' knowledge that the majority of mothers' knowledge about formula milk had sufficient knowledge as many as 30 respondents (50%) and a minority of well-informed mothers were 5 respondents (8.3%), the majority of their husbands' support was poor as many as 40 respondents (66.7% ) and the minority whose husband's support was good as many as 20 respondents (33.3%), the majority of the support from the health workers was not good as many as 39 respondents (65%) and the minority whose support from the health personnel was good as many as 21 respondents (35%). The conclusion of this study shows that there is a relationship between knowledge, husband support and support from health workers with formula milk feeding for infants 0-6 months in Pangurabaan Village, Sipirok District, South Tapanuli Regency in 2020. formula in infants and can provide information to mothers who have babies 0-6 months so as not to give formula milk too early.